Changes in acid-base and ion balance during exercise in normoxia and normobaric hypoxia - Lühker, Olaf; Berger, Marc Moritz; Pohlmann, Alexander; Hotz, Lorenz; Gruhlke, Tilmann; Hochreiter, Marcel (European journal of applied physiology, 2017)
PurposeBoth exercise and hypoxia cause complex changes in acid-base homeostasis. The aim of the present study was to investigate whether during intense physical exercise in normoxia and hypoxia, the modified physicochemical approach offers a better understanding of the changes in acid-base homeostasis than the traditional Henderson-Hasselbalch approach.MethodsIn this prospective, randomized, crossover trial, 19 healthy males completed an exercise test until voluntary fatigue on a bicycle ergometer on two different study days, once during normoxia and once during normobaric hypoxia (12% oxygen, equivalent to an altitude of 4500 m). Arterial blood gases were sampled during and after the exercise test and analysed according to the modified physicochemical and Henderson-Hasselbalch approach, respectively.ResultsPeak power output decreased from 287 ± 9 Watts in normoxia to 213 ± 6 Watts in hypoxia (−26%, P < 0.001). Exercise decreased arterial pH to 7.21 ± 0.01 and 7.27 ± 0.02 (P < 0.001) during normoxia and hypoxia, respectively, and increased plasma lactate to 16.8 ± 0.8 and 17.5 ± 0.9 mmol/l (P < 0.001). While the Henderson-Hasselbalch approach identified lactate as main factor responsible for the non-respiratory acidosis, the modified physicochemical approach additionally identified strong ions (i.e. plasma electrolytes, organic acid ions) and non-volatile weak acids (i.e. albumin, phosphate ion species) as important contributors.ConclusionsThe Henderson-Hasselbalch approach might serve as basis for screening acid-base disturbances, but the modified physicochemical approach offers more detailed insights into the complex changes in acid-base status during exercise in normoxia and hypoxia, respectively.